2014
DOI: 10.1155/2014/465694
|View full text |Cite
|
Sign up to set email alerts
|

Role of Microglia Adenosine A2AReceptors in Retinal and Brain Neurodegenerative Diseases

Abstract: Neuroinflammation mediated by microglial cells in the brain has been commonly associated with neurodegenerative diseases. Whether this microglia-mediated neuroinflammation is cause or consequence of neurodegeneration is still a matter of controversy. However, it is unequivocal that chronic neuroinflammation plays a role in disease progression and halting that process represents a potential therapeutic strategy. The neuromodulator adenosine emerges as a promising targeting candidate based on its ability to regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 187 publications
(192 reference statements)
2
69
0
Order By: Relevance
“…In the "activated state" the cell morphology is more ameboid and they exhibit pseudopodia (Davis et al, 1994). In healthy conditions microglia are found at variable densities in the different retinal layers, including the NFL, ganglion cell layer (GCL), inner plexiform layer (IPL), inner nuclear layer (INL) and OPL Cuenca et al, 2014;Garcia-Valenzuela et al, 2005;Noailles et al, 2014;Santiago et al, 2014;Sobrado-Calvo et al, 2007). The cells have a small ovoid-shaped cell body and multiple ramifications in the GCL of the normal retina, and they are organized into a single sheet that is distributed homogeneously (Garcia-Valenzuela et al, 2005).…”
Section: Origin Morphology and Distribution Of Microgliamentioning
confidence: 99%
“…In the "activated state" the cell morphology is more ameboid and they exhibit pseudopodia (Davis et al, 1994). In healthy conditions microglia are found at variable densities in the different retinal layers, including the NFL, ganglion cell layer (GCL), inner plexiform layer (IPL), inner nuclear layer (INL) and OPL Cuenca et al, 2014;Garcia-Valenzuela et al, 2005;Noailles et al, 2014;Santiago et al, 2014;Sobrado-Calvo et al, 2007). The cells have a small ovoid-shaped cell body and multiple ramifications in the GCL of the normal retina, and they are organized into a single sheet that is distributed homogeneously (Garcia-Valenzuela et al, 2005).…”
Section: Origin Morphology and Distribution Of Microgliamentioning
confidence: 99%
“…15 Therapeutic potential of adenosine receptor-based therapy for ROP is supported by the ability of adenosine receptors to modulate inflammation, neuroprotection, and angiogenesis in retina through activation of four G-protein-coupled receptors, namely, A 1 , A 2A , A 2B , and A 3 , all of which have been detected in retina. 16,17 Increased adenosine acting at A 2A Rs suppresses neuroinflammation and protects against diabetic retinopathy (DR) 18 and traumatic optic neuropathy, 19 through control of retinal microglial function and production of proinflammatory cytokines 20,21 ; studies with genetic inactivation of the A 2A R, 15 with A 2B R antagonists [22][23][24] and with ribozyme approach to inactivating A 2B Rs, demonstrate that adenosine acting at the A 2A and A 2B receptors promotes pathologic angiogenesis in retina through modulating VEGF level. 25 The translational potential of adenosine receptor-based therapy for controlling proliferative retinopathy is substantiated by a clinical potential, since a recent large clinical trial of 2006 infants has demonstrated that treatment with caffeine, a nonselective adenosine receptor antagonist, reduces ROP-related problems after 2-year follow-up, 26 and by genetic identification of the variants of the human A 2A R gene that are associated with reduced risk of developing DR in a prospective study.…”
mentioning
confidence: 99%
“…Age-related neurodegenerative diseases of the brain and retina appear to share similar mechanisms [105], and a growing body of evidence demonstrates that microglia-mediated neuroinflammation plays a key role in the pathophysiology of both brain and retinal diseases [80]. …”
Section: Resultsmentioning
confidence: 99%
“…The involvement of nonneuronal cells in several noxious conditions has been examined in more detail. Several reports demonstrate that the mechanism by which the blockade of A 2A R confers neuroprotection is through the control of microglia-mediated neuroinflammation [for a revision, see [80]]. In fact, some aspects of neuroprotection observed with the blockade of A 2A R may involve direct actions in microglia.…”
Section: A2ar Blockade: Potential Therapeutic Strategy For Neuroprotementioning
confidence: 99%